2013
DOI: 10.1177/0278364913481690
|View full text |Cite
|
Sign up to set email alerts
|

Ground fluidization promotes rapid running of a lightweight robot

Abstract: We study the locomotor mechanics of a small, lightweight robot (DynaRoACH, 10 cm, 25 g) which can move on a granular substrate of 3 mm diameter glass particles at speeds up to 5 body length/s, approaching the performance of certain desert-dwelling animals. To reveal how the robot achieves this performance, we used high-speed imaging to capture its kinematics, and developed a numerical multi-body simulation of the robot coupled to an experimentally validated simulation of the granular medium. Average speeds mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…DEM allows one to obtain information such as forces and flow fields of the granular media that were difficult to measure in experiment. Particularly when coupled with a multi-body dynamic simulator, DEM has been useful in describing body-media interactions during locomotion, facilitating parameter variation and the development of locomotor principles [128,221,256,257].…”
Section: Simulating Granular Media Demmentioning
confidence: 99%
See 1 more Smart Citation
“…DEM allows one to obtain information such as forces and flow fields of the granular media that were difficult to measure in experiment. Particularly when coupled with a multi-body dynamic simulator, DEM has been useful in describing body-media interactions during locomotion, facilitating parameter variation and the development of locomotor principles [128,221,256,257].…”
Section: Simulating Granular Media Demmentioning
confidence: 99%
“…In contrast, high frequency gaits induced speed-dependent hydrodynamic-like forces resulting from inertial drag, allowing the robot to achieve rapid running on the leg-fluidized substrate. Zhang et al [257] also demonstrated the capabilities of DEM simulation for parameter variation by varying the coefficients of particle particle friction, particle leg friction, and leg width over a wide range, and tested the effects of these parameters on robot locomotion performance. The particle friction parameters are difficult to vary continuously and independently of other parameters in experiment.…”
Section: Simulating Granular Media Demmentioning
confidence: 99%
“…Many small legged animals (16)(17)(18)(19) [and increasingly robots (20)(21)(22)(23)] face the challenges of moving on natural substrates such as sand (16,17,21), gravel (16,20), rubble (20), soil (20,22),mud (17,20), snow (18,20), grass (20,22), and leaf litter (19,20,22), which, unlike solid ground, can flow during movement when a yield stress is exceeded. The complexity of the interactions with such flowable ground may rival or even exceed that during movement in fluids.…”
mentioning
confidence: 99%
“…Our approach affords significant reduction in the computational time needed to model movement on granular media. For example, relative to our multiparticle discrete element method (DEM) simulation of movement on granular media (23,27), our simulation using the resistive force model can achieve a factor of 10 6 in speed-up (e.g., 10 s versus 30 days using DEM to simulate 1 s of locomotion on a granular bed of 5 × 10 6 poppy seeds).…”
mentioning
confidence: 99%
“…The mechanism traverses granular media at speeds of up to 30 cm/s or 5 body lengths per second. In units of body lengths per second our mechanism speed is similar to the the six legged DynaRoACH robot (10 cm long, 25 g) [28], but slower than the zebra-tailed lizard (10 cm long, 10g) that can move 10 body lengths/s [27]. Our mechanism horizontal speed exceeds many conventional bristle bots, has no external moving parts and can traverse flat granular media.…”
Section: Summary and Discussionmentioning
confidence: 81%